QSAR treatment of meisoindigo derivatives as a potentbreast anticancer agent - Evie Kama Lestari; Agus Dwi Ananto; Maulida Septiyana; Saprizal Hadisaputra (Chemistry Education Program, the University of Mataram, 2019)
A quantitative structure-activity relationship (QSAR) analysis of meisoindigo derivatives as a breast anticancer has been carried out. This study aimed to obtain the best QSAR model in order to design new meisoindigo based compounds with best anticancer activity. The semiempirical PM3 method was used for descriptor calculation. The best QSAR model was built using multilinear regression (MLR) with enter method. It was found that there were 19 new meisoindigo derivativeswith better predictive a potent anticancer agent. The best compound was (E)-2-(1-((3-ethylisoxazol-5-yl)methyl)-2-oxoindolin-3-ylidene)-N-(4-methoxyphenyl)acetamide with the value of IC505.31144 x10-15 (Î¼M).